Multi-layer composite pedestrian steel bridge pavement structure and construction method
By adopting a multi-layer composite paving structure on the pedestrian steel bridge, combined with materials such as epoxy resin, polyurethane resin and asphalt mixture, the existing pedestrian steel bridges have solved the problems of poor weather resistance, insufficient aesthetics and unsatisfactory walking comfort, achieving efficient waterproof, anti-slip and weather resistance, and being convenient to construct.
Patent Information
- Application Number
- CN202510118115.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-03-21
AI Technical Summary
The existing pedestrian steel bridges have problems such as poor weather resistance, insufficient aesthetics, poor walking comfort and poor construction convenience.
The multi-layer composite pedestrian steel bridge paving structure is adopted, including the base layer, anti-rust layer, waterproof bonding layer, gravel particles, paving structure layer, permeable sealing layer, anti-slip layer and stain-resistant surface layer. Through the combination of materials such as epoxy resin, polyurethane resin and asphalt mixture, it forms efficient waterproof, anti-slip and weather resistance.
It achieves good weather resistance, aesthetics and walking comfort, light weight and convenient construction, and improves the overall life and use effect of the bridge deck paving.
Smart Images

Figure CN119663732A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of pedestrian steel bridges, and in particular relates to a multi-layer composite pedestrian steel bridge pavement structure and a construction method. Background Art
[0002] Pedestrian steel bridge is a bridge built with steel as the main material. It has the characteristics of high strength, light weight, and fast construction. It is widely used in urban roads (pedestrian overpasses, flyovers), park landscapes, etc. At present, pedestrian steel bridges generally have defects such as poor weather resistance, insufficient aesthetics, unsatisfactory walking comfort, and poor construction convenience. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide a multi-layer composite pedestrian steel bridge pavement structure and a construction method. The pedestrian steel bridge pavement structure provided by the present invention has good weather resistance, aesthetics and walking comfort, and is light in weight and easy to construct.
[0004] The present invention provides a multi-layer composite pedestrian steel bridge pavement structure, comprising a base layer, an anti-rust layer, a waterproof bonding layer, crushed stone particles, a pavement structure layer, a permeable sealing layer, an anti-skid layer and a stain-resistant surface layer arranged in sequence from bottom to top;
[0005] The base layer is a steel plate;
[0006] The anti-rust layer is an epoxy zinc-rich primer coating;
[0007] The waterproof bonding layer is an epoxy resin coating, and its coating composition includes epoxy resin, filler and curing agent;
[0008] The particle size of the crushed stone particles is ≤5mm;
[0009] The pavement structure layer is a flexible asphalt layer, and its composition is a dense graded asphalt mixture with an asphalt content of 5 to 8 wt%;
[0010] The penetration sealing layer is an epoxy modified polyurethane resin coating, and its coating components include epoxy modified polyurethane resin, filler, curing agent and catalyst;
[0011] The anti-skid layer is an acrylic modified polyurethane resin coating with a rough surface, and its coating ingredients include acrylic modified polyurethane resin, anti-skid particles, wear-resistant filler, curing agent, catalyst and color powder;
[0012] The anti-fouling surface layer is a transparent polyurethane coating, and its coating components include polyurethane resin, acrylic resin and UV absorber.
[0013] Preferably, the zinc content of the epoxy zinc-rich primer coating is ≥70wt%; and the thickness of the epoxy zinc-rich primer coating is 50-100 μm.
[0014] Preferably, in the epoxy resin coating, the epoxy resin is bisphenol A epoxy resin, the filler is silicon dioxide, and the mass ratio of the epoxy resin to the filler is 100:(70-150); the thickness of the epoxy resin coating is 1-2 mm.
[0015] Preferably, the amount of crushed stone particles is 2-3 kg / m 2 .
[0016] Preferably, the dense-graded asphalt mixture comprises asphalt and aggregate; and the thickness of the flexible asphalt layer is 25 to 35 mm.
[0017] Preferably, in the epoxy-modified polyurethane resin coating, the filler is silicon dioxide, and the mass ratio of the epoxy-modified polyurethane resin to the filler is 55:(5-15); and the thickness of the epoxy-modified polyurethane resin coating is 0.2-0.5 mm.
[0018] Preferably, in the acrylic modified polyurethane resin coating, the anti-slip particles are aluminum oxide, the wear-resistant filler is silicon carbide, and the mass ratio of the acrylic modified polyurethane resin, the anti-slip particles and the wear-resistant filler is 60:(10-20):(1-5); the thickness of the acrylic modified polyurethane resin coating is 4-6 mm.
[0019] Preferably, in the transparent polyurethane coating, the mass ratio of the polyurethane resin, the acrylic resin and the UV absorber is 60:(10-30):(0.5-2); and the thickness of the transparent polyurethane coating is 0.2-0.4 mm.
[0020] The present invention provides a construction method of the multi-layer composite pedestrian steel bridge pavement structure described in the above technical solution, comprising the following steps:
[0021] Apply epoxy zinc-rich primer on one side of the steel plate and cure it to form an anti-rust layer;
[0022] Coating epoxy resin coating on the surface of the anti-rust layer and curing it to form a waterproof bonding layer;
[0023] Sprinkling crushed stone particles on the surface of the waterproof bonding layer, and then spreading and compacting the dense-graded asphalt mixture to form a paving structure layer;
[0024] Applying epoxy modified polyurethane resin coating on the surface of the pavement structure layer and curing it to form a permeable sealing layer;
[0025] The surface of the penetration sealing layer is coated with an acrylic modified polyurethane resin coating, and the coating is cured to form an anti-skid layer base; then the surface of the anti-skid layer base is sprayed with anti-skid convex dots using the acrylic modified polyurethane resin coating as a raw material, and the coating is cured to form a rough surface, thereby obtaining an anti-skid layer;
[0026] A transparent polyurethane coating is coated on the surface of the anti-slip layer and cured to form a stain-resistant surface layer, thereby obtaining a multi-layer composite pedestrian steel bridge pavement structure.
[0027] Preferably, the construction method further comprises the following steps:
[0028] Before applying the epoxy zinc-rich primer, the surface of the steel plate to be coated is first subjected to shot blasting to remove rust;
[0029] Before applying the epoxy modified polyurethane resin coating, the surface of the paving structure layer is firstly subjected to shot blasting to remove the oil film.
[0030] Compared with the prior art, the present invention provides a multi-layer composite pedestrian steel bridge pavement structure and a construction method. The multi-layer composite pedestrian steel bridge pavement structure provided by the present invention comprises a base layer, an anti-rust layer, a waterproof bonding layer, crushed stone particles, a pavement structure layer, a permeable sealing layer, an anti-skid layer and a stain-resistant surface layer which are arranged in sequence from bottom to top; the base layer is a steel plate; the anti-rust layer is an epoxy zinc-rich primer coating; the waterproof bonding layer is an epoxy resin coating, and its coating components include epoxy resin, filler and curing agent; the particle size of the crushed stone particles is ≤5mm; the pavement structure layer is a flexible asphalt layer, and its components are a dense-graded asphalt mixture with an asphalt content of 5 to 8wt%; the permeable sealing layer is an epoxy-modified polyurethane resin coating, and its coating components include epoxy-modified polyurethane resin, filler, curing agent and catalyst; the anti-skid layer is an acrylic modified polyurethane resin coating with a rough surface, and its coating components include acrylic modified polyurethane resin, anti-skid particles, wear-resistant filler, curing agent, catalyst and color powder; the stain-resistant surface layer is a transparent polyurethane coating, and its coating components include polyurethane resin, acrylic resin and UV absorber. The pedestrian steel bridge pavement structure provided by the present invention has good weather resistance, aesthetics and walking comfort, and is light in weight and convenient in construction. More specifically, it has the following advantages:
[0031] (1) Strong waterproof and anti-seepage capabilities. The multi-layer composite structure (epoxy waterproof layer system, asphalt pavement structure layer and polyurethane surface layer system) has waterproof and anti-seepage capabilities, effectively improving the life of the pavement structure and even the bridge deck itself.
[0032] (2) It has strong deformation coordination ability and is not easy to crack. It also has the effect of waterproofing and durability. The pavement structure gradually becomes softer from bottom to top, which meets the deformation requirements of the bridge body under load, and the structural level is reasonable.
[0033] (3) Strong interlayer bonding ability and good pavement structure integrity. The anti-rust layer and waterproof bonding layer are both epoxy systems, and the penetration sealing layer, anti-skid layer, and anti-fouling surface layer are all polyurethane systems. The material application is reasonable; special treatment is also performed between different materials. For example, crushed stone particles are sprinkled between the asphalt pavement structure layer and the waterproof bonding layer as bonding and shear-resistant aggregates, and the surface of the asphalt pavement structure layer is preferably treated with shot blasting to remove oil film.
[0034] (4) Good visual effect and reduced maintenance costs. The anti-skid layer is mixed with color powder and a stain-resistant surface layer is set to ensure long-term beauty; the polyurethane surface layer avoids direct exposure of the asphalt paving structure layer and avoids the presence of a large number of pores that are easy to accumulate dirt.
[0035] (5) Good pedestrian comfort. The road adopts a high asphalt content (high oil-to-stone ratio), densely distributed flexible asphalt paving structure layer, combined with a modified polyurethane anti-skid layer, which combines comfort and anti-skid performance.
[0036] (6) Low construction difficulty and cost. The functional layer can be coated or sprayed, with low requirements for flatness and thickness; the paving structure layer is a single layer of asphalt mixture, which is produced by factory hot mixing process and can be constructed with professional construction machinery, and the quality is easy to control.
[0037] (7) Light weight. The thickness of the pavement layer can be designed to be relatively thin, which is light and effectively reduces the load on the bridge body. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0039] Figure 1 It is a schematic diagram of a multi-layer composite pedestrian steel bridge pavement structure provided in an embodiment of the present invention.
[0040] Explanation of the reference numerals: 1 is the base layer, 2 is the anti-rust layer, 3 is the waterproof bonding layer, 4 is the crushed stone particles, 5 is the paving structure layer, 6 is the penetration sealing layer, 7 is the anti-skid layer, and 8 is the stain-resistant surface layer. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The present invention provides a multi-layer composite pedestrian steel bridge pavement structure, such as Figure 1 As shown, it includes a base layer, an anti-rust layer, a waterproof bonding layer, crushed stone particles, a paving structure layer, a permeable sealing layer, an anti-skid layer and a stain-resistant surface layer which are arranged in sequence from bottom to top.
[0043] In the pavement structure provided by the present invention, the base layer is a steel plate; the surface cleanliness of the steel plate preferably reaches Sa2.5 level; the surface roughness of the steel plate preferably reaches 60 to 100 μm, specifically 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm or 100 μm.
[0044] In the pavement structure provided by the present invention, the anti-rust layer is an epoxy zinc-rich primer coating; the zinc content of the epoxy zinc-rich primer coating is preferably ≥70wt%; the thickness of the epoxy zinc-rich primer coating is preferably 50 to 100μm, specifically 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm or 100μm.
[0045] In the pavement structure provided by the present invention, the waterproof bonding layer is an epoxy resin coating, and its coating components include epoxy resin, filler and curing agent. In the present invention, the epoxy resin is preferably bisphenol A epoxy resin, more preferably bisphenol A epoxy resin E-51; the filler is preferably silicon dioxide; the particle size of the filler is preferably 10 to 100 nm, specifically 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm; the mass ratio of the filler to the epoxy resin is preferably (70 to 150):100, specifically 70:100, 80:100, 90:100, 100:100, 110:100, 120:100, 130:100, 140:100 or 150:100; the curing agent is preferably a polyamide curing agent, more preferably polyamide curing agent 650 or polyamide curing agent 651; the mass ratio of the curing agent to the epoxy resin is preferably (20-30):100, specifically 20:100, 21:100, 22:100, 23:100, 24:100, 25:100, 26:100, 27:100, 28:100, 29:100 or 30:100. In the present invention, the coating composition corresponding to the epoxy resin coating preferably also includes an auxiliary agent, including but not limited to one or more of a plasticizer, a coupling agent, a defoaming agent and a accelerator; the plasticizer is preferably diisononyl phthalate (DINP) and / or polyethylene terephthalate-1,4-cyclohexane dimethanol ester (PETG); the mass ratio of the plasticizer to the epoxy resin is preferably (10-20):100, specifically 10:100, 11:100, 12:100, 13:100, 14:100, 15:100, 16:100, 17:100, 18:100, 19:100 or 20:100; the coupling agent is preferably γ-methacryloxypropyltrimethoxysilane (GPTMS) and / or 3-aminopropyltrimethoxysilane (PTMS). Ethoxysilane (APTES); the mass ratio of the coupling agent to the epoxy resin is preferably (1-5):100, specifically 1:100, 2:100, 3:100, 4:100 or 5:100; the defoamer is preferably polydimethylsiloxane (PDMS); the mass ratio of the defoamer to the epoxy resin is preferably (1-5):100, specifically 1:100, 2:100, 3:100, 4:100 or 5:100; the accelerator is preferably triethanolamine (TEA) and / or 2-ethyl-4-methylimidazole (EMI); the mass ratio of the accelerator to the epoxy resin is preferably (2-8):100, specifically 2:100, 3:100, 4:100, 5:100, 6:100, 7:100 or 8:100.In the present invention, the thickness of the epoxy resin coating is preferably 1 to 2 mm, specifically 1 mm, 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm or 2 mm.
[0046] In the paving structure provided by the present invention, the main materials of the waterproof bonding layer and the anti-rust layer are both epoxy resin, which has good material matching items and ensures the interlayer bonding strength between the two.
[0047] In the paving structure provided by the present invention, in the waterproof bonding layer, it is preferred to control its glass transition temperature (Tg) at 100°C (±30°C) by selecting a polyamide curing agent and adjusting the filler ratio, so as to ensure that the high temperature during the paving process of the paving structure layer can soften the waterproof bonding layer, thereby ensuring effective bonding between the layers.
[0048] In the pavement structure provided by the present invention, the particle size of the crushed stone particles is ≤5mm; the crushed stone particles are usually selected from limestone particles or basalt particles, and basalt particles with higher hardness are the best choice; the amount of the crushed stone particles is 2-3kg / m 2 , specifically 2kg / m 2 , 2.1kg / m 2 , 2.2kg / m 2 , 2.3kg / m 2 , 2.4kg / m 2 , 2.5kg / m 2 , 2.6kg / m 2 , 2.7kg / m 2 , 2.8kg / m 2 , 2.9kg / m 2 or 3kg / m 2 .
[0049] In the pavement structure provided by the present invention, the pavement structure layer is a flexible asphalt layer, and its component is a dense-graded asphalt mixture. In the present invention, the components of the dense-graded asphalt mixture are asphalt and aggregate, wherein the content of asphalt is 5-8wt%, specifically 5wt%, 5.5wt%, 6wt%, 6.5wt%, 6.6wt%, 7wt%, 7.5wt% or 8wt%. In the present invention, the asphalt is preferably an ultra-high viscosity modified asphalt, which is prepared from SBS modified asphalt and high-viscosity particles, wherein the SBS modified asphalt is prepared from base asphalt, SBS modifier, rubber oil and stabilizer. In the present invention, the base asphalt is preferably 70# asphalt; the amount of the SBS modifier is preferably 5-10wt% of the mass of the base asphalt, specifically 7wt%; the amount of the rubber oil is preferably 1-5wt% of the mass of the base asphalt, specifically 3wt%; the amount of the stabilizer is preferably 0.1-1wt% of the mass of the base asphalt, specifically 0.5wt%; the amount of the high-viscosity particles is preferably 1-5wt% of the mass of the SBS modified asphalt, specifically 2.5wt%.
[0050] In the pavement structure provided by the present invention, the aggregate in the flexible asphalt layer includes 3-5 mm coarse mineral material, 0-3 mm fine mineral material and mineral powder; wherein the content of the 3-5 mm coarse mineral material is preferably 27-33wt%, specifically 30.5wt%, the content of the 0-3 mm fine mineral material is preferably 60-65wt%, specifically 63wt%, and the mineral powder is the remainder.
[0051] In the pavement structure provided by the present invention, the thickness of the flexible asphalt layer is preferably 25-35 mm, specifically 25 mm, 26 mm, 27 mm, 28 mm, 29 mm, 30 mm, 31 mm, 32 mm, 33 mm, 34 mm or 35 mm.
[0052] In the pavement structure provided by the present invention, the permeable sealing layer is mainly used to improve the waterproof performance of the pavement structure, prevent water from penetrating the pavement structure, reduce the erosion of water on the roadbed, extend the service life of the bridge deck pavement, and play a certain role in crack resistance. In the present invention, the permeable sealing layer adopts epoxy modified polyurethane resin coating, which has good elasticity and permeability, can adapt to the slight deformation of the road surface, reduce the risk of cracking, and resist cracking caused by temperature changes and traffic loads, and can produce good interlayer bonding with the flexible asphalt layer. In the present invention, the coating components corresponding to the epoxy-modified polyurethane resin coating include epoxy-modified polyurethane resin, filler, curing agent and catalyst; wherein the filler is preferably silicon dioxide; the particle size of the filler is preferably 10 to 100 nm, specifically 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm or 100 nm; the mass ratio of the filler to the epoxy-modified polyurethane resin is preferably (5 to 15):55, specifically 5:55, 6:55, 7:55, 8:55, 9:55, 10:55, 11:55, 12:55, 13:55, 14:55 or 15:55; the curing agent is preferably a polyisocyanate curing agent , more preferably diphenylmethane diisocyanate (MDI); the mass ratio of the curing agent to the epoxy-modified polyurethane resin is preferably (15-25):55, specifically 15:55, 16:55, 17:55, 18:55, 19:55, 20:55, 21:55, 22:55, 23:55, 24:55 or 25:55; the catalyst is preferably dibutyltin dilaurate; the mass ratio of the catalyst to the epoxy-modified polyurethane resin is preferably (0.5-2):55, specifically 0.5:55, 0.6:55, 0.7:55, 0.8:55, 0.9:55, 1:55, 1.1:55, 1.2:55, 1.5:55, 1.7:55 or 2:55.In the present invention, the coating component corresponding to the epoxy-modified polyurethane resin coating preferably also includes an auxiliary agent, including but not limited to one or more of a defoamer, a leveling agent and a wetting agent; the defoamer is preferably a polyether-modified silicone oil; the mass ratio of the defoamer to the epoxy-modified polyurethane resin is preferably (0.1-1):55, specifically 0.1:55, 0.2:55, 0.3:55, 0.4:55, 0.5:55, 0.6:55, 0.7:55, 0.8:55, 0.9:55 or 1:55; the leveling agent is preferably an organic siloxane; the mass ratio of the leveling agent to the epoxy-modified polyurethane resin is preferably (0.1-1):55. It is preferably (0.5-2):55, specifically 0.5:55, 0.6:55, 0.7:55, 0.8:55, 0.9:55, 1:55, 1.1:55, 1.2:55, 1.5:55, 1.7:55 or 2:55; the wetting agent is preferably a phosphate compound; the mass ratio of the wetting agent to the epoxy-modified polyurethane resin is preferably (0.1-1):55, specifically 0.1:55, 0.2:55, 0.3:55, 0.4:55, 0.5:55, 0.6:55, 0.7:55, 0.8:55, 0.9:55 or 1:55. In the present invention, the coating component corresponding to the epoxy-modified polyurethane resin coating preferably further includes a solvent; the solvent is preferably acetone; the mass ratio of the solvent to the epoxy-modified polyurethane resin is preferably (7-20):55, specifically 7:55, 8:55, 9:55, 10:55, 11:55, 12:55, 13:55, 14:55, 15:55, 16:55, 17:55, 18:55, 19:55 or 20:55. In the present invention, the thickness of the epoxy-modified polyurethane resin coating is preferably 0.2-0.5 mm, specifically 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm or 0.5 mm.
[0053] In the pavement structure provided by the present invention, the anti-skid layer is mainly used to improve the walking and visual comfort of the pedestrian bridge deck, and at the same time has a certain anti-seepage and waterproof effect; the anti-skid layer is an acrylic modified polyurethane resin coating with a rough surface, which uses the same substrate as the penetration sealing layer to ensure mutual adhesion between the two, and the acrylic modification can significantly improve the coating's resistance to ultraviolet rays, and has good adhesion and flexibility. In the present invention, the coating components corresponding to the acrylic modified polyurethane resin coating include acrylic modified polyurethane resin, anti-skid particles, wear-resistant fillers, curing agents, catalysts and toners; wherein the anti-skid particles are preferably aluminum oxide; the particle size of the anti-skid particles is preferably 0.1 to 0.5 mm, specifically 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm or 0.5 mm; the mass ratio of the anti-skid particles to the acrylic modified polyurethane resin is preferably (10 to 20):60, specifically 10:60, 11:60, 12:60, 13:60, 14:60, 15:60, 16:60, 17:60, 18:60, 19:60 or 20:60; the wear-resistant filler is preferably silicon carbide; the particle size of the wear-resistant filler is preferably 0.1-0.3 mm, specifically 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm or 0.3 mm; the mass ratio of the wear-resistant filler to the acrylic modified polyurethane resin is preferably (1-5):60, specifically 1:60, 1.5:60, 2:60, 2.5:60, 3:60, 3.5:60 , 4:60, 4.5:60 or 5:60; the curing agent is preferably a polyisocyanate curing agent, more preferably diphenylmethane diisocyanate (MDI); the mass ratio of the curing agent to the acrylic modified polyurethane resin is preferably (15-25):60, specifically 15:60, 16:60, 17:60, 18:60, 19:60, 20:60, 21:60, 22:60, 23:60, 24:60 or 25:60; the catalyst is preferably dibutyltin dilaurate; the catalyst and the acrylic modified polyurethane resin are preferably 1:60, 2:60, 2:60, 2:60, 2:60, 2:60, 2:60, 2:60, 2:60, 2:60, 2:60 or 2:60. The mass ratio of lipids is preferably (0.5-2):60, specifically 0.5:60, 0.6:60, 0.7:60, 0.8:60, 0.9:60, 1:60, 1.1:60, 1.2:60, 1.5:60, 1.7:60 or 2:60; the amount of color powder added is adjusted according to the color saturation. Generally speaking, the amount of color powder added is controlled at 1-10wt% of the total mass of the coating, the amount of light-colored color powder added is usually 1-3wt%, the amount of medium-colored color powder added is usually 3-6wt%, and the amount of dark-colored color powder added is usually 6-10wt%.In the present invention, the coating component corresponding to the acrylic modified polyurethane resin coating preferably further includes an auxiliary agent, including but not limited to one or more of a defoamer, a leveling agent and a wetting agent; the defoamer is preferably a polyether modified silicone oil; the mass ratio of the defoamer to the acrylic modified polyurethane resin is preferably (0.1-1):60, specifically 0.1:60, 0.2:60, 0.3:60, 0.4:60, 0.5:60, 0.6:60, 0.7:60, 0.8:60, 0.9:60 or 1:60; the leveling agent is preferably an organic siloxane; the mass ratio of the leveling agent .... The amount ratio is preferably (0.5-2):60, specifically 0.5:60, 0.6:60, 0.7:60, 0.8:60, 0.9:60, 1:60, 1.1:60, 1.2:60, 1.5:60, 1.7:60 or 2:60; the wetting agent is preferably a phosphate compound; the mass ratio of the wetting agent to the epoxy-modified polyurethane resin is preferably (0.1-1):60, specifically 0.1:60, 0.2:60, 0.3:60, 0.4:60, 0.5:60, 0.6:60, 0.7:60, 0.8:60, 0.9:60 or 1:60. In the present invention, the coating component corresponding to the acrylic modified polyurethane resin coating preferably further includes a solvent; the solvent is preferably acetone; the mass ratio of the solvent to the epoxy modified polyurethane resin is preferably (0.5-2):60, specifically 0.5:60, 0.6:60, 0.7:60, 0.8:60, 0.9:60, 1:60, 1.1:60, 1.2:60, 1.5:60, 1.7:60 or 2:60. In the present invention, the thickness of the acrylic modified polyurethane resin coating is preferably 4-6 mm, specifically 4 mm, 4.5 mm, 5 mm, 5.5 mm or 6 mm.
[0054] In the pavement structure provided by the present invention, the anti-fouling surface layer is a transparent polyurethane coating, and its coating components include polyurethane resin, acrylic resin and UV absorber. In the present invention, the mass ratio of the polyurethane resin to the acrylic resin is preferably 60:(10-30), specifically 60:10, 60:11, 60:12, 60:13, 60:14, 60:15, 60:16, 60:17, 60:18, 60:19, 60:20, 60:21, 60:22, 60:23, 60:24, 60:25, 60:26, 60:27, 60:28, 60:29 or 60:30; the UV absorber is preferably Tinuvin P; The mass ratio of the UV absorber to the polyurethane resin is preferably (0.5-2):60, specifically 0.5:60, 0.6:60, 0.7:60, 0.8:60, 0.9:60, 1:60, 1.1:60, 1.2:60, 1.5:60, 1.7:60 or 2:60. In the present invention, the anti-fouling surface layer is a transparent polyurethane coating, and the corresponding coating components preferably further include one or more of a diluent, a leveling agent, an antioxidant and a defoaming agent; the diluent is preferably ethyl acetate; the mass ratio of the diluent to the polyurethane resin is preferably (10-20):60, specifically 10:60, 11:60, 12:60, 13:60, 14:60, 15:60, 16:60, 17:60, 18:60, 19:60 or 20:60; the leveling agent is preferably an organosiloxane; the mass ratio of the leveling agent to the polyurethane resin is preferably (0.5-5):60, specifically 0.5:60, 1:60, 1.5:60, 2:60, 2.5:60, 3:60, 3.5:60, 4:60, 4.5:60 or 5:60; the antioxidant is preferably Irganox 1010; the mass ratio of the antioxidant to the polyurethane resin is preferably (0.5-2):60, specifically 0.5:60, 0.6:60, 0.7:60, 0.8:60, 0.9:60, 1:60, 1.1:60, 1.2:60, 1.5:60, 1.7:60 or 2:60; the defoamer is preferably polyether modified silicone oil; the mass ratio of the defoamer to the polyurethane resin is preferably (0.5-2):60, specifically 0.5:60, 0.6:60, 0.7:60, 0.8:60, 0.9:60, 1:60, 1.1:60, 1.2:60, 1.5:60, 1.7:60 or 2:60. In the present invention, the thickness of the transparent polyurethane coating is preferably 0.2-0.4 mm, specifically 0.2 mm, 0.23 mm, 0.25 mm, 0.27 mm, 0.3 mm, 0.32 mm, 0.35 mm, 0.37 mm or 0.4 mm.
[0055] The present invention also provides a construction method of the multi-layer composite pedestrian steel bridge pavement structure described in the above technical solution, comprising the following steps:
[0056] Apply epoxy zinc-rich primer on one side of the steel plate and cure it to form an anti-rust layer;
[0057] Coating epoxy resin coating on the surface of the anti-rust layer and curing it to form a waterproof bonding layer;
[0058] Sprinkling crushed stone particles on the surface of the waterproof bonding layer, and then spreading and compacting the dense-graded asphalt mixture to form a paving structure layer;
[0059] Applying epoxy modified polyurethane resin coating on the surface of the pavement structure layer and curing it to form a permeable sealing layer;
[0060] The surface of the penetration sealing layer is coated with an acrylic modified polyurethane resin coating, and the coating is cured to form an anti-skid layer base; then the surface of the anti-skid layer base is sprayed with anti-skid convex dots using the acrylic modified polyurethane resin coating as a raw material, and the coating is cured to form a rough surface, thereby obtaining an anti-skid layer;
[0061] A transparent polyurethane coating is coated on the surface of the anti-slip layer and cured to form a stain-resistant surface layer, thereby obtaining a multi-layer composite pedestrian steel bridge pavement structure.
[0062] In the construction method provided by the present invention, before applying the epoxy zinc-rich primer, the surface of the steel plate to be coated is preferably subjected to shot blasting to remove rust. The surface cleanliness of the steel plate after the shot blasting should reach Sa2.5 level, and the roughness should reach 60-100 μm, ensuring that the rust is removed very thoroughly, and the surface should be free of visible grease, dirt, scale, rust, paint coating and other attachments.
[0063] In the construction method provided by the present invention, after the steel plate completes the shot blasting and rust removal, the epoxy zinc-rich primer should be coated as soon as possible to complete the rust prevention treatment. The time allowed should be controlled within 2 hours, the high humidity or salt environment should be controlled within 4 hours, the environment with large temperature difference or high temperature should be controlled within 6 hours, and the rust prevention treatment should be completed within 24 hours under normal circumstances.
[0064] In the construction method provided by the present invention, the coating method of the epoxy zinc-rich primer is preferably scraping, and more preferably single-pass scraping. In the present invention, the coating dry film thickness (i.e., the thickness of the anti-rust layer) of the epoxy zinc-rich primer is preferably 50 to 100 μm, and the corresponding coating amount of the epoxy zinc-rich primer is preferably controlled at 0.15 to 0.4 kg / m 2 Generally speaking, a 50μm dry film thickness requires approximately 0.15 to 0.2kg / m 2 Epoxy zinc-rich primer, 100μm dry film thickness requires about 0.3~0.4kg / m 2Epoxy zinc-rich primer.
[0065] In the construction method provided by the present invention, the coating method of the epoxy resin coating is preferably scraping; the coating dry film thickness of the epoxy resin coating (i.e., the thickness of the waterproof bonding layer) is preferably 1 to 2 mm, and the corresponding coating amount is preferably controlled at 1 to 2 kg / m 2 .
[0066] In the construction method provided by the present invention, the paving speed of the dense-graded asphalt mixture is preferably 1.5-2.0 m / min; the paved dense-graded asphalt mixture is preferably initially compacted at above 150°C, and then re-compacted 2-4 times by a horizontal oscillating roller, followed by 1-2 times of final compaction by a steel wheel roller without vibration, and finally compacted by a manual motorized rammer at the edge.
[0067] In the construction method provided by the present invention, before applying the epoxy modified polyurethane resin coating, it is preferred to first perform shot blasting on the surface of the paving structure layer to remove the oil film, and further increase the aggregate roughness to improve the bonding performance between layers. In the present invention, after the shot blasting is completed, it is required that the surface layer has no asphalt oil film, the asphalt aggregate is exposed, and visually manifested as alternating black and white particles.
[0068] In the construction method provided by the present invention, the coating method of the epoxy-modified polyurethane resin coating is preferably scraping; the coating dry film thickness of the epoxy-modified polyurethane resin coating (i.e., the thickness of the permeable sealing layer) is preferably 0.2 to 0.5 mm, and the corresponding coating coating amount is preferably controlled at 200 to 500 g / m 2 .
[0069] In the construction method provided by the present invention, the coating method of the acrylic modified polyurethane resin coating is preferably scraping; the coating dry film thickness of the acrylic modified polyurethane resin coating (i.e., the thickness of the anti-slip layer base layer) is preferably 3.5-4.5 mm, and the corresponding coating amount is preferably controlled at 3.5-4.5 kg / m 2 The anti-skid convex point spraying treatment is preferably carried out in two times, and the second spraying is carried out after the first layer is cured; the construction angle of the anti-skid convex point spraying treatment is preferably controlled at 40-50°, specifically 40°, 45° or 50°; the coating amount of the anti-skid convex point spraying treatment is preferably 1.2-1.5 kg / m 2 .
[0070] In the construction method provided by the present invention, the transparent polyurethane coating is preferably applied by spraying; the coating amount of the transparent polyurethane coating is preferably controlled to be 0.2-0.4 kg / m 2 .
[0071] The technical solution provided by the present invention can obtain a multi-layer composite pedestrian steel bridge pavement structure with good performance and convenient construction. More specifically, it has the following key points and advantages:
[0072] (I) Adopting multi-layer composite structure to improve the rationality of pedestrian steel bridge deck pavement structure:
[0073] (1) Combining the advantages of polymer paving and asphalt paving. Use polymer materials as the functional layer of the pavement structure to give full play to its characteristics of anti-seepage and waterproofing, strong permeability, and good deformation ability; use asphalt concrete as the pavement structure layer and optimize its mix ratio to achieve the characteristics of softness, comfort, anti-seepage and waterproofing;
[0074] (2) Polymer materials are selected as the functional layer, which is thin and easy to construct. Specifically, it includes the epoxy waterproof layer system at the bottom (epoxy zinc-rich primer layer and waterproof bonding layer) and the polyurethane surface layer system (penetration sealing layer, anti-slip layer and anti-fouling surface layer);
[0075] (3) Epoxy materials have the characteristics of high strength, good impermeability, high hardness and stable chemical properties, but they are easily oxidized and have insufficient weather resistance. They can only be used as the base structure to give full play to their advantages;
[0076] (4) Polyurethane materials have the characteristics of high strength, high toughness, wear resistance, good adhesion, and high weather resistance, which can ensure effective bonding with the paving structure layer, and have better durability when directly in contact with the external environment;
[0077] (5) Flexible asphalt pavement as a pavement structure layer has the characteristics of softness, comfort, durability and anti-seepage;
[0078] (II) Improve the weather resistance of steel bridges and optimize the water resistance and anti-seepage capabilities of bridge deck pavement:
[0079] (1) On the basis of setting up the epoxy waterproof layer system, a flexible asphalt mixture with high asphalt content (high oil-stone ratio) and dense distribution is used as the pavement structure layer, which has good waterproof and anti-seepage capabilities;
[0080] (2) Avoid direct exposure of the asphalt pavement structure layer to the outdoor environment. Set up a polyurethane surface layer system. The penetration sealing layer has good waterproof and anti-seepage capabilities. At the same time, the polyurethane anti-slip layer and anti-fouling surface layer also have good weather resistance and water repellency, effectively protecting the pavement structure layer, improving the overall weather resistance of the steel bridge, and ensuring the overall life of the bridge deck pavement.
[0081] (III) Improving the aesthetics and comfort of bridge deck pavement:
[0082] (1) Use a colored anti-slip layer and a stain-resistant surface layer containing UV absorbers to ensure aesthetics and color fastness;
[0083] (2) Using high asphalt content (high asphalt-to-stone ratio) and densely distributed flexible asphalt mixture as the pavement structure layer, which provides good pedestrian comfort;
[0084] (3) The anti-skid layer is made of high-friction, high-flexibility polyurethane material and adopts a double-layer anti-skid spray process to further optimize pedestrian comfort;
[0085] (4) Through the setting of the polyurethane surface layer system, the walking comfort characteristics of the flexible asphalt pavement structure layer can be fully utilized while avoiding the characteristics of asphalt pavement with many pores and easy to absorb pollution.
[0086] (IV) Optimize construction performance and reduce construction difficulty and cost:
[0087] (1) Through shot blasting to remove rust, shot blasting to remove oil film, bonding shear-resistant aggregates, and coatings on the same substrate (epoxy system, polyurethane system), the bonding ability between the various layers of materials is improved to ensure the construction performance of the pavement structure;
[0088] (2) The paving structure layer adopts mature factory hot mix technology and can be constructed using conventional large-scale paving equipment. The performance, flatness, thickness and other construction stability of the finished product are well controlled;
[0089] (3) The process of "single paving structure layer paving and multifunctional layer coating" is adopted. The paving structure layer is thicker and is the key factor affecting the flatness and thickness. The single paving structure layer can ensure the flatness and thickness of the bridge deck as much as possible; the functional layers are all coated with paint, which has almost no effect on thickness and flatness.
[0090] (V) Light weight, strong crack resistance, good deformation ability, reducing the impact of bridge deformation on the pavement structure:
[0091] (1) The process of "single paving structure layer paving and multifunctional layer coating" is adopted. The paving structure layer is thin and the weight of the functional layer can be ignored, thus reducing the overall deadweight of the paving structure;
[0092] (2) From the steel plate base to the top pavement, the flexibility of each layer of structure is gradually improved, the overall deformation is more coordinated, and the anti-cracking effect is better;
[0093] (3) The epoxy waterproof layer has a certain flexibility and is applied on the steel plate with greater rigidity, so it can adapt to the deformation of the bridge body;
[0094] (4) The asphalt pavement structure layer adopts a flexible mix ratio with high asphalt content and has good crack resistance;
[0095] (5) Polyurethane material has good flexibility and can be used as a surface layer to adapt to the coupled deformation of the bridge body and the pavement structure layer;
[0096] For the purpose of greater clarity, the invention is described in detail through the following embodiments.
[0097] Example 1
[0098] A kind of Figure 1 The multi-layer composite pedestrian steel bridge pavement structure and construction method shown are described in detail as follows:
[0099] (1) Shot blasting and rust removal of base layer
[0100] 1. The particle size of steel shot is S-170~S-280, the particle size of steel sand is G-16~G-25, and the sand-shot ratio is determined according to the on-site test section;
[0101] 2. The surface cleanliness of the steel plate base layer is required to reach Sa2.5 level and the roughness is required to reach 60-100μm to ensure thorough rust removal. The surface should be free of visible grease, dirt, oxide scale, rust, paint coating and other attachments.
[0102] (ii) Anti-rust coating
[0103] 1. After the base steel plate is shot blasted and rust-proofed, the anti-rust layer should be scraped as soon as possible. The time allowed should be controlled within 2 hours. The high humidity or salt environment should be controlled within 4 hours. The environment with large temperature difference or high temperature should be controlled within 6 hours. Under normal circumstances, the anti-rust treatment should be completed within 24 hours;
[0104] 2. Use epoxy zinc-rich primer as the anti-rust layer treatment material, and the zinc content of the primer is higher than 70wt%;
[0105] 3. Use scraping technology for construction, use single-layer coating, the dry film thickness is controlled at 80μm, and the corresponding paint dosage is controlled at 0.3kg / m 2 .
[0106] (III) Waterproof adhesive layer scraping
[0107] 1. The components of the waterproof bonding layer include epoxy resin, filler, curing agent, plasticizer, coupling agent, defoaming agent and accelerator;
[0108] 2. Epoxy resin is bisphenol A epoxy resin E-51;
[0109] 3. Silicon dioxide (particle size 60nm) is used as filler to enhance the toughness and impact resistance of the waterproof bonding layer;
[0110] 4. Use polyamide curing agent as curing agent, specifically 650#;
[0111] 5. PETG is used as plasticizer; APTES is used as coupling agent; PDMS is used as defoamer; EMI is used as accelerator;
[0112] 6. The weight ratio of each component is: epoxy resin: curing agent: filler: plasticizer: coupling agent: defoamer (leveling agent): accelerator = 100:25:100:20:5:4:5;
[0113] 7. Use scraping technology to construct the waterproof bonding layer, the dry film thickness is controlled at 2mm, and the corresponding coating amount is controlled at 2kg / m 2 ;
[0114] 8. By selecting polyamide curing agent and adjusting the filler ratio, the glass transition temperature (Tg) is controlled between 100℃ (±30℃), ensuring that the high temperature during the paving process of the paving structure layer can soften the waterproof bonding layer to ensure effective bonding between layers;
[0115] 9. The main materials of the waterproof bonding layer and the anti-rust layer are epoxy resin, which has good material matching and ensures the interlayer bonding strength between the two.
[0116] (IV) Spreading of bonded shear-resistant aggregate
[0117] 1. The particle size of the bonded shear-resistant aggregate (crushed stone particles) should be less than 5 mm, and basalt should be used;
[0118] 2. The surface of aggregates must be clean, free of dust, sand and impurities;
[0119] 3. The amount of aggregate spread is controlled at 2.5kg / m 2 .
[0120] (V) Paving and rolling of the structural layer
[0121] 1. The pavement structure layer uses a hot-mix flexible asphalt mixture with high asphalt content and dense distribution, and the asphalt content is 6.6wt%;
[0122] 2. The asphalt in the asphalt mixture is ultra-high viscosity modified asphalt, and the preparation method is: 70# base asphalt + 7% SBS modifier + 0.5% stabilizer + 3% rubber oil are used to prepare the modified asphalt, and then 2.5% high viscosity particles are added to the modified asphalt to prepare the ultra-high viscosity modified asphalt. The technical indicators of the ultra-high viscosity modified asphalt are shown in Table 1:
[0123] Table 1 Ultra-high viscosity modified asphalt indicators
[0124]
[0125]
[0126] 3. Aggregates in asphalt mixture include: 0-3mm fine aggregate (accounting for 63%), 3-5mm coarse aggregate (accounting for 30.5%), and mineral powder (accounting for 6.5%). The technical indicators of 3-5mm coarse aggregate, 0-3mm fine aggregate and aggregate as a whole are shown in Table 2, Table 3, and Table 4 respectively:
[0127] Table 2 Coarse ore (3-5 mm) indicators
[0128]
[0129] Table 3 Index of fine ore (0~3mm)
[0130]
[0131] Table 4 Overall index of aggregate
[0132]
[0133]
[0134] 4. The technical indicators of asphalt mixture are shown in Table 5:
[0135] Table 5 Dense graded asphalt mixture index
[0136] Test items unit Test results Technical requirements Marshall specimen relative density - 2.425 Measured Stability kN 9.83 ≥5.0 Stream Value 0.1mm 2.6 2.0-5.0 Porosity % 2.1 2.0-3.0 Asphalt saturation % 82 70-90 Kentucky Fort Scattering % 1.9 ≤8 Rutting test Times / mm 8256 ≥3000 Permeability ml / s 22 ≤60 Freeze-thaw splitting strength ratio % 91.9 ≥80
[0137] 5. Use special mechanical equipment for construction, with a paving thickness of 30mm and a paving speed of 1.5m / min. Complete the initial compaction at above 150℃, use a horizontal oscillating roller for 2 to 4 times, and use a steel wheel roller for 1 to 2 times without vibration for the final compaction. Use a manual motorized rammer to compact the edges.
[0138] (VI) Shot blasting treatment of the surface of the pavement structure layer
[0139] 1. Shot blasting on the surface of the pavement structure layer is mainly to remove the asphalt oil film on the surface, further increase the roughness of the aggregate, and improve the bonding performance between layers;
[0140] 2. Mix steel shot and steel grit in a certain proportion as shot material. Considering that the asphalt is thicker, the proportion of steel grit needs to be slightly higher than that of steel shot, using 60wt%:40wt%.
[0141] (VII) Penetration sealing layer coating (polyurethane)
[0142] 1. The penetration sealing layer is mainly used to improve the waterproof performance of the pavement structure, prevent water from penetrating the pavement structure, reduce the erosion of water on the roadbed, extend the service life of the bridge deck pavement, and play a certain role in crack resistance;
[0143] 2. The permeable sealing layer adopts modified polyurethane resin permeable sealing layer. This material has good elasticity and permeability, can adapt to the slight deformation of the road surface, reduce the risk of cracking, and resist cracking caused by temperature changes and traffic loads. It can produce good interlayer bonding with the modified asphalt sealing layer;
[0144] 3. The weight ratio of each component is 55:20:1:0.5:1:0.5:10:12: polyurethane resin (epoxy modified): polyisocyanate curing agent (MDI): catalyst (dibutyltin dilaurate): defoaming agent (polyether modified silicone oil): leveling agent (organic siloxane): wetting agent (phosphate ester compound): fine filler (silicon dioxide, particle size 60nm): solvent (acetone);
[0145] 4. Use scraping technology for construction, the thickness is controlled at 0.3mm, and the corresponding coating amount is controlled at 300g / m 2 ;
[0146] 5. The technical indicators of the penetration sealing layer are shown in Table 6:
[0147] Table 6 Indicators of penetration sealing layer (epoxy modified polyurethane resin coating)
[0148] project Technical requirements Tensile strength (MPa, 25℃) ≥5.0 Elongation at break (%, 25°C) ≥20 Water resistance No abnormal phenomenon after immersion in water for 24 hours Alkali resistance No abnormal phenomenon after immersion in saturated calcium hydroxide solution for 24 hours Low temperature crack resistance of coating -10℃ for 4h, 4h for one cycle, no cracks after three consecutive cycles
[0149] (VIII) Anti-slip layer coating (polyurethane)
[0150] 1. The anti-slip coating is mainly used to improve the walking and visual comfort of the pedestrian bridge deck, and also has a certain anti-seepage and waterproof effect;
[0151] 2. The anti-slip coating uses modified polyurethane anti-slip coating (acrylic acid modified), which uses the same substrate as the penetration sealing layer to ensure mutual adhesion between the two. Acrylic acid modification can significantly improve the coating's resistance to ultraviolet rays and has good adhesion and flexibility;
[0152] 3. The weight ratio of each component is: polyurethane resin (acrylic modified): polyisocyanate curing agent (TDI): catalyst (dibutyltin dilaurate): defoaming agent (polyether modified silicone oil): leveling agent (organic siloxane): wetting agent (phosphate ester compound): anti-slip particles (aluminum oxide, particle size 0.1-0.5mm): wear-resistant filler (silicon carbide, particle size 0.1-0.3mm): solvent (acetone) = 60:20:1:0.5:1:0.5:15:2:1;
[0153] 4. The amount of color powder added is adjusted according to the color saturation. In this embodiment, the amount of color powder added in the coating is controlled at 6%;
[0154] 5. Use scraping technology for construction, the thickness should be controlled at 3.5mm, and the corresponding coating amount should be controlled at 3.5kg / m 2 ;
[0155] 6. The technical indicators of the anti-slip coating are shown in Table 7:
[0156] Table 7 Anti-slip coating (epoxy modified polyurethane resin coating) indicators
[0157]
[0158]
[0159] (IX) Anti-slip spray treatment (polyurethane)
[0160] 1. The material selection for anti-slip spraying is the same as that for anti-slip coating, which is implemented in two steps. The second spraying is carried out after the first step is cured.
[0161] 2. The spraying angle is controlled at 45° and the coating dosage is controlled at 1.4kg / m 2 ;
[0162] 3. The overall thickness of the anti-slip layer obtained after anti-slip spray treatment (anti-slip coating + spray) is about 5mm.
[0163] (10) Anti-fouling surface spraying (polyurethane)
[0164] 1. The anti-fouling surface layer adopts transparent polyurethane coating, and the components are matched by weight: polyurethane resin (polyester polyurethane): acrylic resin (to improve weather resistance and transparency): diluent (ethyl acetate): leveling agent (organic siloxane): antioxidant (Irganox 1010): defoaming agent (polyether modified silicone oil): UV absorber (TinuvinP) = 60:20:15:2:1:1:1;
[0165] 2. The anti-fouling topcoat is applied by spraying technology, the thickness should be controlled at 0.4mm, and the corresponding coating dosage should be controlled at 0.4kg / m 2 .
[0166] (XI) Overall performance evaluation of the multi-layer composite pedestrian steel bridge pavement structure, the results are shown in Table 8:
[0167] Table 8 Overall pavement structure quality inspection
[0168]
[0169] In Table 8, JTG E60 is the "Field Test Procedure for Highway Roadbed and Pavement", and JTG / T3364-02 is the "Technical Specification for Design and Construction of Highway Steel Bridge Deck Pavement".
[0170] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A multi-layer composite pedestrian steel bridge pavement structure, characterized in that: It includes a base layer, an anti-rust layer, a waterproof bonding layer, crushed stone particles, a paving structure layer, a permeable sealing layer, an anti-skid layer and a stain-resistant surface layer arranged in sequence from bottom to top; The base layer is a steel plate; The anti-rust layer is an epoxy zinc-rich primer coating; The waterproof bonding layer is an epoxy resin coating, and its coating composition includes epoxy resin, filler and curing agent; The particle size of the crushed stone particles is ≤5mm; The pavement structure layer is a flexible asphalt layer, and its composition is a dense graded asphalt mixture with an asphalt content of 5 to 8 wt%; The penetration sealing layer is an epoxy modified polyurethane resin coating, and its coating components include epoxy modified polyurethane resin, filler, curing agent and catalyst; The anti-skid layer is an acrylic modified polyurethane resin coating with a rough surface, and its coating ingredients include acrylic modified polyurethane resin, anti-skid particles, wear-resistant filler, curing agent, catalyst and color powder; The anti-fouling surface layer is a transparent polyurethane coating, and its coating components include polyurethane resin, acrylic resin and UV absorber.
2. The multi-layer composite pedestrian steel bridge pavement structure according to claim 1 is characterized in that: The zinc content of the epoxy zinc-rich primer coating is ≥70wt%; the thickness of the epoxy zinc-rich primer coating is 50-100μm.
3. The multi-layer composite pedestrian steel bridge pavement structure according to claim 1 is characterized in that: In the epoxy resin coating, the epoxy resin is bisphenol A epoxy resin, the filler is silicon dioxide, and the mass ratio of the epoxy resin to the filler is 100:(70-150); the thickness of the epoxy resin coating is 1-2 mm.
4. The multi-layer composite pedestrian steel bridge pavement structure according to claim 1 is characterized in that: The amount of crushed stone particles is 2-3 kg / m 2 .
5. The multi-layer composite pedestrian steel bridge pavement structure according to claim 1 is characterized in that: The dense-graded asphalt mixture comprises asphalt and aggregate; the thickness of the flexible asphalt layer is 25 to 35 mm.
6. The multi-layer composite pedestrian steel bridge pavement structure according to claim 1 is characterized in that: In the epoxy-modified polyurethane resin coating, the filler is silicon dioxide, and the mass ratio of the epoxy-modified polyurethane resin to the filler is 55:(5-15); the thickness of the epoxy-modified polyurethane resin coating is 0.2-0.5 mm.
7. The multi-layer composite pedestrian steel bridge pavement structure according to claim 1 is characterized in that: In the acrylic modified polyurethane resin coating, the anti-skid particles are aluminum oxide, the wear-resistant filler is silicon carbide, and the mass ratio of the acrylic modified polyurethane resin, the anti-skid particles and the wear-resistant filler is 60:(10-20):(1-5); the thickness of the acrylic modified polyurethane resin coating is 4-6 mm.
8. The multi-layer composite pedestrian steel bridge pavement structure according to claim 1 is characterized in that: In the transparent polyurethane coating, the mass ratio of polyurethane resin, acrylic resin and UV absorber is 60:(10-30):(0.5-2); the thickness of the transparent polyurethane coating is 0.2-0.4 mm.
9. A construction method for the multi-layer composite pedestrian steel bridge pavement structure according to any one of claims 1 to 8, characterized in that: The following steps are involved: Apply epoxy zinc-rich primer on one side of the steel plate and cure it to form an anti-rust layer; Coating epoxy resin coating on the surface of the anti-rust layer and curing it to form a waterproof bonding layer; Sprinkling crushed stone particles on the surface of the waterproof bonding layer, and then spreading and compacting the dense-graded asphalt mixture to form a paving structure layer; Applying epoxy modified polyurethane resin coating on the surface of the pavement structure layer and curing it to form a permeable sealing layer; The surface of the penetration sealing layer is coated with an acrylic modified polyurethane resin coating, and the coating is cured to form an anti-skid layer base; then the surface of the anti-skid layer base is sprayed with anti-skid convex dots using the acrylic modified polyurethane resin coating as a raw material, and the coating is cured to form a rough surface, thereby obtaining an anti-skid layer; A transparent polyurethane coating is coated on the surface of the anti-slip layer and cured to form a stain-resistant surface layer, thereby obtaining a multi-layer composite pedestrian steel bridge pavement structure.
10. The construction method according to claim 9, characterized in that: Also includes: Before applying the epoxy zinc-rich primer, the surface of the steel plate to be coated is first subjected to shot blasting to remove rust; Before applying the epoxy modified polyurethane resin coating, the surface of the paving structure layer is firstly subjected to shot blasting to remove the oil film.